Study of Tourist Satisfaction to Experience Quality of Visit to Budapest, Hungary, as Cultural Heritage Destination - Vicentius Bagas Adi Pratama (Program Studi Pariwisata Fakultas Ilmu Budaya Universitas Gadjah Mada Yogyakarta, 2020)
The goal of this research is to determine the level of satisfaction of tourists who visited Budapest as a cultural heritage tourism destination in terms of experience quality, which includes interaction quality, physical environment quality, access quality, and outcome quality. In this study, the holiday satisfaction (HOLSAT) model is used to examine tourist satisfaction levels by comparing the mean of expectation and experience from each attribute. In total, 131 on-line questioners’ responses from international tourists who visited Budapest between October 24 and November 17, 2019 were collected. The findings show that there are seven attributes indicating tourist satisfaction: staff knowledge, language competence, preservation, sign & information, ease of access, public transportation, and safety & security. Technology, traffic, and crowdedness are three indicators of tourist dissatisfaction. Furthermore, service, staff interaction, exhibition display, facilities, cleanliness, site accessibility, unpleasant behaviour of other visitors, and learning experience have a less significant difference between expectation and experience